Desain Perancangan Buck Converter Berbasis IC LM2596 - Raka Dian Mahardi; Lilo Sunuharjo; Danang Hendrawan; Muhammad ‘Atiq; Rizal Agri Wahyuadi; Sigit Prakosa Adhi Nugraha (Politeknik Kampar, 2024)
A buck converter is a circuit that functions to reduce DC-DC voltage which is often used in various electronic applications. The aim of this research is to design and implement a buck converter circuit that utilizes the LM2596 IC. The research methodology includes circuit design and practical testing. The research results show that circuit testing was carried out with input voltage variations of 10V, 15V, and 20V, which produced stable output voltages of 6.68V, 6.71V, and 6.78V respectively.